Improving Classroom Communication: The Effects of Virtual Social Training on Communication and Assertion Skills in Middle School Students - Johnson, Maria Teresa; Troy, Aimee Herron; Tate, Kathleen Michelle; Allen, Tandra Toon; Tate, Aaron Michael; Chapman, Sandra Bond (Frontiers in Education, 2021)
This study examined the relationship between teacher identification of socially at-risk adolescents and baseline student social competency levels. Additionally, the feasibility and effects of an eight-session, virtual social training were analyzed. Upon completion of the virtual social training, the transfer effects from the targeted intervention into the general education classroom were determined. Study participants (N=90) were comprised of sixth, seventh and eighth-grade students from four public middle schools in Dallas, Texas. Data was collected through classroom teacher questionnaires to measure students’ baseline social behaviors. In addition, pre-post student performance measures in the areas of affect recognition, social inference, and social attribution were administered. Results revealed that middle school teachers were effective identifiers of students with lagging social skills. Baseline ratings of social skills showed a high positive association between student affect recognition and teacher rating of participant total social skills including communication, cooperation, responsibility, and self-control. A high negative association was found between student affect recognition and problem behaviors. A high negative association was also found between student perspective-taking and hyperactivity and externalizing behaviors. Student pre-post test performance measures revealed significant improvement in affect recognition, attribution, and social inferencing after undergoing the virtual social training. At the time of a five-week follow up, teachers rated participants' social skills in the areas of communication and assertion as significantly improved. Sixty-eight percent of participants reported increased confidence in social communication skills such as relating, maintaining, adapting, and asserting thoughts after the training. Preliminary findings from this small-scale study provide evidence that a brief eight-session, virtual social training in middle school is a feasible delivery model that can achieve positive effects on social behavior, and that teacher referral was a reliable way to identify students who could benefit from the training. Incorporating teacher perspective aided in translating a previously lab-based training into an ecologically relevant setting while addressing a programming need to meet the social demands of adolescence.